ESL design and verification : a prescription for electronic system-level methodology - Bailey, Brian, 1959- (Morgan Kaufmann series in systems on silicon., 2007)
Electronic System Level (ESL) design has mainstreamed it is now an established approach at most of the worlds leading system-on-chip (SoC) design companies and is being used increasingly in system design. From its genesis as an algorithm modeling methodology with no links to implementation, ESL is evolving into a set of complementary methodologies that enable embedded system design, verification and debug through to the hardware and software implementation of custom SoC, system-on-FPGA, system-on-board, and entire multi-board systems. This book arises from experience the authors have gained from years of work as industry practitioners in the Electronic System Level design area; they have seen "SLD" or "ESL" go through many stages and false starts, and have observed that the shift in design methodologies to ESL is finally occurring. This is partly because of ESL technologies themselves are stabilizing on a useful set of languages being standardized (SystemC is the most notable), and use models are being identified that are beginning to get real adoption. ESL DESIGN & VERIFICATION offers a true prescriptive guide to ESL that reviews its past and outlines the best practices of today. Visit the authors' companion site! http://www.electronicsystemlevel.com/ * Provides broad, comprehensive coverage not available in any other such book * Massive global appeal with an internationally recognised author team * Crammed full of state of the art content from notable industry experts